2020
DOI: 10.7717/peerj.8412
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic analysis of very early onset pancreatic cancer: a population-based analysis

Abstract: Background. We aimed to use competing risk model to assess whether very early onset pancreatic cancer (VEOPC ) (<45 years) had a worse prognosis than older pancreatic cancer (PC) patients, and to build a competing risk nomogram for predicting the risk of death of VEOPC. Methods. We selected pancreatic adenocarcinoma (PDAC) patients as our cohort from the Surveillance, Epidemiology, and End Results (SEER) database. The impact of cancer specific death was estimated by competing risk analysis. Multivariate Fine-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The higher the LNR stage, the lower the CSS. Dai et al confirmed similarly that a higher LNR was an independent prognostic factor of CSS based on their retrospective study of 1,386 pancreatic cancer (<45 years) (6). LNR has been also regarded as an independent prognostic factor that is strongly associated with the prognosis of various malignancies such as oral cancer, esophageal cancer, breast cancer and medullary thyroid cancer, etc (45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The higher the LNR stage, the lower the CSS. Dai et al confirmed similarly that a higher LNR was an independent prognostic factor of CSS based on their retrospective study of 1,386 pancreatic cancer (<45 years) (6). LNR has been also regarded as an independent prognostic factor that is strongly associated with the prognosis of various malignancies such as oral cancer, esophageal cancer, breast cancer and medullary thyroid cancer, etc (45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 85%
“…Currently, there is no international standard definition of early onset pancreatic cancer. In recent years, early onset pancreatic cancer has been defined in literatures as pancreatic cancer diagnosed before the age of 40, 45, 50 years (5)(6)(7)(8). Considering that researchers often use the criterion of age < 50 years for EOPC in literatures and the American Gastrointestinal Association Institute recommended that screening for pancreatic cancer in high-risk groups should begin at age 50, we have defined EOPC as pancreatic cancer diagnosed at an age of less than 50 years in this study (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Our prediction model comprehensively considers all stages of ovarian cancer and suggests three "early" death periods (1, 3, and 6 months) as references. The prognosis of malignant tumors of the digestive tract is mostly related to race, marital status, and tumor location, which has been shown using nomograms [11][12][13][14]. Unlike most human cancers that spread through blood-borne metastasis, traditionally, EOC tumor cells were considered to metastasize directly by migrating through the peritoneal fluid to the omentum of the peritoneal cavity, highlighting its unique metastasis compared with that in lung cancer [15], breast cancer [16] and other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Backward stepwise regression based on Bayesian information criteria was conducted to select independent risk factors and avoid overfitting. A competing risk model was then constructed using the Fine and Gray proportional sub-distribution hazards regression model for different types of CMM ( 21 , 22 ). Nomograms were established based on the independent risk factors to estimate the 3-, 5-, and 10-year probability of death resulting from CMM, other cancers, and noncancerous diseases.…”
Section: Methodsmentioning
confidence: 99%